Translation into Brazilian Portuguese and validation of the M-CHAT-R/F scale for early screening of autism spectrum disorder - Losapio,Mirella Fiuza (2023)
ABSTRACT Objective: To translate and validate the Modified Checklist for Autism in Toddlers, Revised with Follow-Up (M-CHAT-R/F) from English to Brazilian Portuguese, taking transcultural differences into account. Methods: Permission for the translation was obtained from the author of the scale. Translation and back-translation were performed, and the document was then assessed for reference and general equivalence. Specialists in childhood autism evaluated the scale. A preliminary version was prepared and pre-tested in a sample population, and a final version was validated with the target population. Results: Only one question had issues relating to referential equivalence. The 10 individuals questioned in the pre-test all understood most of the instrument, although some suggested substituting certain terms to improve comprehension. The final version was reached following inclusion of pertinent suggestions and was submitted to validation with the target population, indicating a sensitivity of 88.2% for a cutoff point greater than 2 points. Conclusions: A Brazilian version of the M-CHAT-R/F scale, approved by specialists and understandable by the target audience, is now available for use.